Problems of Recycling and Utilization of Household and Industrial Waste in the Coastline of Batumi - Loria, Madona; Maia Tughushi (Georgian Maritime Scientific Journal, 2024)
Development of the infrastructure of the Black Sea coastal zone is one of the priority directions of Georgia. In order to increase the potential of the tourism sector, it is important to improve the ecological conditions of the Black Sea and the coastline. Despite the national environmental protection programme and the current Law on Waste Management, the problem of waste management is still relevant and noteworthy. The seaport and the terminal operating in Batumi strictly protect the requirements foreseen by the "International Convention for the Prevention of Pollution from Ships (MARPOL), 1973.“ Moreover, the Order "Rules for Monitoring the Movement of Ships in the Territorial Sea and Harbor Waters of Georgia and the Functioning of the Information System" has been in force since 2016. The purpose of this rule is to ensure the protection of human life, safety of navigation and protection of the marine environment by using the Vessel Traffic Monitoring System in the territorial sea and access corridors to the ports; detection of potential pollution of the marine environment from ships and their prevention. But despite the mentioned regulatory actions, there is a big problem in terms of waste recycling and utilization. The article discusses the issues that make obstacles for ensuring the compliance with environmental protection norms within the city of Batumi and its surrounding area. The authors, taking into account the international experience of obtaining biogas from waste, propose the possibility of obtaining energy from the waste of the Batumi landfill for the purpose of waste recycling and utilization.